2014
DOI: 10.1155/2014/506482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Environmental Nano- and Macrocolloid Particles Extracted from Selected Soils and Biosolids

Abstract: Environmental nanoparticles found in soil systems and biosolids may pose a considerable risk to groundwater quality as contaminant carriers. Little effort has been invested in the characterization of natural nanocolloids compared to corresponding macrocolloids. This study involved physicochemical, mineralogical, and morphological characterizations of nanocolloids and macrocolloids fractionated from three Kentucky soils and one biosolid. Particle size and morphology were investigated using scanning/transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…Another type of nanoparticle/nanostructures formed has darker colors, with no definition of edges and a lumpy shape (Figures 2 and 3). This shape description resembles that in the study of Ghezzi et al (2014), who related it to Fe oxides. In almost all treatments except T6, the hexagonal and lumpy nanoparticles seem interconnected in some places.…”
Section: T2 T10supporting
confidence: 73%
See 3 more Smart Citations
“…Another type of nanoparticle/nanostructures formed has darker colors, with no definition of edges and a lumpy shape (Figures 2 and 3). This shape description resembles that in the study of Ghezzi et al (2014), who related it to Fe oxides. In almost all treatments except T6, the hexagonal and lumpy nanoparticles seem interconnected in some places.…”
Section: T2 T10supporting
confidence: 73%
“…Selvíria, Mato Grosso do Sul, Brazil. The solutions collected during sonication were subsequently centrifuged (model NT 815, NOVATECNICA ®) for 36 min at 4,970 rpm at 20ºC, to separate structures and particles smaller than 200nm (Ghezzi et al, 2014). After centrifugation, 25 mL of the supernatant was removed and filled in a plastic jar at 4°C (Tang et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that colloids are present in OW. For example, nano-ZnS is a major Zn species in raw liquid OW (Kim et al, 2014;Le Bars et al, 2018), and organic colloids have been observed in biosolids (Ghezzi et al, 2014).…”
Section: Colloidal Transfer For Trace Element Leaching Predictionmentioning
confidence: 99%